KARAKTERISTIK DAN POTENSI PERKEMBANGAN KAWASAN KOMERSIAL SEGITIGA PANDAMA (PANDANARANâGAJAHMADAâPEMUDA) DI KOTA SEMARANG - Wibowo, Soni Akbar; Haryanto, Ragil (Jurnal Pengembangan Kota, 2013)
Pandanaran, Gajahmada, and Pemuda (Pandama region) in recent years continued to experience growth in property investment, especially for commercial functions and show more rapid growth in the region. The growth phenomenon of the Pandama triangle areas as an investment destination and as a leading commercial center business is growing in line with the shift in the investment market (market force) that reacts to the many problems and limitations of Simpang Lima area as the destination investment CBD driven by previous Semarang Municipality. The research was carried out with quantitative approach to determine the characteristics and potential development of Pandama commercial areas in the future. Commercial activity in the Pandama triangle dominated by service function by 58% with the pattern of development and distribution of commercial activity in th triangle Pandama tends to change from a pattern that follows the road network (ribbon) to be concentrated pattern (center). Pandama triangular commercial area in the future will grow an develop as a magnet development in Semarang city and impact the higher quantity growth of the commercial activity and also lead to increasing the land conversion level of settlement into a commercial.